Comparative evaluation of intrathecal hyperbaric 0.75% ropivacaine with hyperbaric 0.5% bupivacaine in lower limb orthopaedic surgeries: A prospective randomized double blind study - Santosh Choudhary; Khemraj Meena; Monika Saharan; Sandeep Sharma; Vikram Bedi; Astha Negi (The Indian Anaesthetists' Forum)
Background and Aims: Recently, hyperbaric 0.75% ropivacaine has been made commercially available. We planned this study to compare the effect of intrathecal hyperbaric 0.75% ropivacaine and hyperbaric 0.5% bupivacaine in spinal anesthesia for lower limb orthopedic surgeries. Materials and Methods: Patients were randomly allocated into 2 groups of 40 patients each – -Group B and R to receive subarachnoid block with 0.5% hyperbaric bupivacaine 15 mg and 0.75% hyperbaric ropivacaine 22.5 mg, respectively. The primary outcome measured was the duration of analgesia. Secondary outcomes measured were onset and duration of sensory-motor block, peak sensory level attained, degree of motor block, time to micturition, and hemodynamic parameters. Categorical, continuous, and ordinal data were presented as number (proportion), mean ± standard deviation and median interquartile range, respectively. Chi-square test, t-test, and Mann–Whitney U-test were applied where deemed appropriate. P < 0.05 was considered statistically significant. Results: Duration of analgesia and sensory and motor block were lesser in ropivacaine group. Mean time for the onset of sensory-motor block was faster in Group B. Patients in ropivacaine group exhibited a shorter time to micturition and a lesser degree of motor block as compared to bupivacaine group. Median peak sensory level and hemodynamic parameters in both groups were statistically comparable. Conclusion: Despite a slower onset time of block and reduced duration of analgesia, intrathecal hyperbaric ropivacaine provides a better alternative to intrathecal hyperbaric bupivacaine for lower limb orthopedic surgeries by providing a shorter duration of sensorimotor block, a lesser degree of motor block, shorter time to first micturition, and a stable hemodynamic profile, thus allowing early ambulation.